Organic electroluminescent material and organic electroluminescent device

By designing specific combinations of heterocyclic ligands and substituents, the energy level structure of organic electroluminescent materials was optimized, solving the problems of luminescence efficiency and stability of green phosphorescent materials, and achieving a reduction in driving voltage and an improvement in quantum efficiency.

CN119285679APending Publication Date: 2025-01-10JILIN OPTICAL & ELECTRONICS MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411269856.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing green phosphorescent materials suffer from low luminescence quantum efficiency and poor color purity, mainly due to the difficulty in designing ligands for heavy metal complexes with narrow band gaps, and the strong π-π bond interactions, which lead to an increase in non-radiative relaxation channels, thus reducing the quantum yield and molecular stability of the phosphorescent system.

Method used

By employing specific combinations of heterocyclic ligands and substituents, and adjusting the position and activity of the substituents, organic electroluminescent materials are designed and synthesized for use as the luminescent layer in organic electroluminescent devices. The energy level structure of the materials is optimized to improve luminous efficiency and stability.

Benefits of technology

The device's driving voltage was reduced, the maximum external quantum efficiency was improved, and the phosphorescence lifetime was extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038384020000011
    Figure BDA0005038384020000011
  • Figure BDA0005038384020000022
    Figure BDA0005038384020000022
  • Figure BDA0005038384020000031
    Figure BDA0005038384020000031
Patent Text Reader

Abstract

The invention provides an organic electroluminescent material and an organic electroluminescent device, and the organic electroluminescent material has a structure shown in a general formula I. The organic electroluminescent material provided by the invention is used for the organic electroluminescent device, and can reduce the driving voltage of the device, improve the maximum external quantum efficiency of the device and prolong the phosphorescence lifetime of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic photoelectric materials and relates to an organic electroluminescent material and an organic electroluminescent device. Background Art

[0002] Organic electroluminescence (OLED) and related research As early as 1963, Pope et al. first discovered the electroluminescence phenomenon of organic compound single crystal anthracene. In 1987, Kodak Company in the United States used the method of evaporating organic small molecules to produce an amorphous film device, which reduced the driving voltage to less than 20V. This type of device has the advantages of ultra-light, fully solidified, self-luminous, high brightness, wide viewing angle, fast response speed, low driving voltage, low power consumption, bright colors, high contrast, simple process, good temperature characteristics, and soft display. It can be widely used in flat panel displays and surface light sources, so it has been widely studied, developed and used.

[0003] At present, green phosphorescent materials still have the problems of low luminescent quantum efficiency and poor color purity. The main reason for this situation is that phosphorescence comes from the transition between energy levels with a narrow energy gap, and there are certain difficulties in the design of ligands for narrow-bandgap heavy metal complexes. Secondly, there is a strong π-π bond interaction in the system of phosphorescent materials, and there is a strong charge transfer characteristic between ligands, which makes more radiation-free relaxation channels exist in the narrow band gap, aggravates the quenching of phosphors, and reduces the quantum yield and molecular stability of phosphorescent systems. Therefore, designing and synthesizing green phosphorescent materials with excellent comprehensive performance will become an important topic in the research of organic electroluminescent materials. Summary of the invention

[0004] In view of this, the present invention provides an organic electroluminescent material and a preparation method thereof and an application in an organic electroluminescent device. The organic electroluminescent material provided by the present invention is used as a material in the light-emitting layer of an organic electroluminescent device, so that the driving voltage of the device can be reduced, the maximum external quantum efficiency of the device can be increased, and the phosphorescence life of the device can be prolonged.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides an organic electroluminescent material having a structure shown in Formula I:

[0007]

[0008] Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14, R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 and R 23 Each is independently selected from any one or a combination of at least two of a hydrogen atom, a deuterium atom, a halogen atom, a cyano group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aralkyl group, a substituted or unsubstituted alkoxy group, a substituted or unsubstituted aryloxy group, a substituted or unsubstituted heteroaryloxy group, a substituted or unsubstituted heterocyclic group, a substituted or unsubstituted silanyl group, a substituted or unsubstituted germyl group, and a substituted or unsubstituted amino group;

[0009] And R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 and R 23 They may optionally combine with adjacent groups to form a ring.

[0010] Preferably, the alkyl, aryl and aralkyl groups may be partially or fully deuterated.

[0011] Furthermore, the LA ligand The following structures are preferred:

[0012]

[0013]

[0014]

[0015] Furthermore, the LB ligand The following structures are preferred:

[0016]

[0017]

[0018]

[0019]

[0020]

[0021] Furthermore, the organic electroluminescent material is preferably selected from the following two structural formulas I-1, I-2, I-3, I-4, I-5, I-6 or I-7:

[0022]

[0023] In the present invention, the organic electroluminescent material is preferably selected from any one of the following structures:

[0024]

[0025]

[0026]

[0027]

[0028]

[0029]

[0030]

[0031]

[0032]

[0033]

[0034]

[0035]

[0036]

[0037]

[0038]

[0039]

[0040]

[0041]

[0042]

[0043]

[0044]

[0045]

[0046]

[0047]

[0048]

[0049]

[0050]

[0051]

[0052]

[0053]

[0054]

[0055]

[0056]

[0057]

[0058]

[0059]

[0060]

[0061]

[0062]

[0063]

[0064]

[0065]

[0066]

[0067]

[0068]

[0069]

[0070]

[0071]

[0072]

[0073]

[0074]

[0075]

[0076]

[0077]

[0078]

[0079]

[0080]

[0081] Only some specific structural forms are listed above, but this series of organic electroluminescent materials is not limited to the above molecular structures. Other specific molecular structures can be obtained by simple changes of some simple groups and their substituted groups and substitution positions, which will not be described one by one here.

[0082] The second object of the present invention is to provide application of the above organic electroluminescent material in an organic electroluminescent device.

[0083] The present invention provides an electroluminescent device, comprising the organic electroluminescent material as described above. The organic electroluminescent device comprises: an anode, a cathode and an organic layer disposed between the anode and the cathode, wherein the organic layer comprises the organic electroluminescent material as described in the present invention; the organic electroluminescent material is in a single form or mixed with other substances and exists in the organic layer.

[0084] The organic layer at least includes a hole injection layer, a hole transport layer, a layer having both hole injection and hole transport skills, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer and a layer having both electron transport and electron injection skills, or a combination of at least two of them.

[0085] The organic electroluminescent device comprises at least one functional layer, namely, the organic electroluminescent material of the present invention.

[0086] The organic electroluminescent device comprises a light-emitting layer, and the light-emitting layer contains the organic electroluminescent material of the present invention.

[0087] The light-emitting layer of the organic electroluminescent device includes a main material and a doping material, wherein the doping material is the organic electroluminescent material of the present invention, and the mixing mass ratio of the main material to the doping material is 90:10 to 99.5:0.5, for example, 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2 or 99:1, etc.

[0088] The device of the present invention can be used in organic light-emitting devices, organic solar cells, electronic paper, organic photoreceptors or organic thin film transistors.

[0089] Compared with the prior art, the present invention has the following beneficial effects:

[0090] The present invention provides an organic electroluminescent material. By selecting a specific heterocyclic ligand for coordination and adjusting the position of a substituent or the activity of a substituent, the obtained organic electroluminescent material is used in an organic electroluminescent device, so that the maximum external quantum efficiency of the device is improved, the life span is prolonged, and the driving voltage is reduced. DETAILED DESCRIPTION

[0091] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0092] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0093] Preparation of Example 1G-2

[0094]

[0095] Step 1: Under a nitrogen atmosphere, 1,2-dibromophenanthrene (59.89 mmol), phenylboric acid (61.08 mmol), anhydrous potassium carbonate (179.67 mmol), toluene (2000 ml), ethanol (1000 ml), and water (2000 ml) were added to the phase system in sequence, and the nitrogen was replaced twice. Under nitrogen protection, tetrakis(triphenylphosphine)palladium (0.5989 mmol) was added to the phase system, and the nitrogen was replaced twice. The reaction was heated to 75°C and refluxed for 10 hours. The heating was turned off, and the mixture was cooled to room temperature and allowed to stand for separation. The aqueous phase was extracted twice with ethyl acetate, and the organic phases were combined, washed with water three times, spin-dried, and subjected to column chromatography. A mixture of petroleum ether and dichloromethane was used as an eluent to obtain intermediate S1 (7.35 g) with a yield of 36.97%.

[0096] Mass spectrometry test value: 332.12.

[0097] 1 H NMR (400 MHz, deuterated chloroform) δ 8.12–8.04 (m, 3H), 7.93–7.87 (m, 2H), 7.71 (d, 1H), 7.56–7.33 (m, 7H).

[0098]

[0099] Step 2: Under a nitrogen atmosphere, the intermediate S1 (60.23 mmol), pyridine-2-boric acid (66.25 mmol), anhydrous potassium carbonate (180.69 mmol), toluene (2000 ml), ethanol (1000 ml), and water (2000 ml) were added to the phase system in sequence, and the nitrogen was replaced twice. Under nitrogen protection, tetrakis(triphenylphosphine)palladium (0.6023 mmol) was added to the phase system, and the nitrogen was replaced twice. The reaction was refluxed at 85°C for 12 hours, and the heating was turned off. The mixture was cooled to room temperature and allowed to stand for separation. The aqueous phase was extracted twice with ethyl acetate, and the organic phases were combined, washed with water three times, spin-dried, and subjected to column chromatography. A mixture of petroleum ether and dichloromethane was used as an eluent to obtain the intermediate S2 (8.97 g). The yield was 44.98%.

[0100] Mass spectrometry test value: 331.25.

[0101]

[0102] Step 3: Under nitrogen protection, weigh formula A-2 (59.09 mmol) and IrC13·3H2O (23.63 mmol) into the reaction system, add a mixed solution of 150 ml of ethylene glycol ethyl ether and 50 ml of pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, a precipitate is precipitated, filter the precipitate, rinse and dry it with water, anhydrous ethanol and petroleum ether in turn, and obtain the bridging ligand B-2 (12.52 g), yield: 94.02%.

[0103] Step 4: Weigh the bridging ligand B-2 (11.09 mmol), add silver trifluoromethanesulfonate (24.39 mmol), then add 200 ml of dichloromethane to the system, add 60 ml of methanol, react at room temperature for 48 hours under nitrogen protection, pass through a silica gel funnel, and spin dry to obtain intermediate C-2 (15.6 g), yield: 95.12%.

[0104] Step 5: Weigh the intermediate C-2 (21.08 mmol), add the ligand S2 (52.7 mmol), and then add 312 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 48 hours, filter, wash with alcohol, and dry. Use a mixture of petroleum ether and dichloromethane as a developing solvent, column chromatography, concentrate the filtrate, and solid precipitate to obtain an organic electroluminescent material G-2 (6.99 g), with a yield of 38.62%.

[0105] HPLC:≥99.3%.

[0106] Mass spectrometry test value: 859.38

[0107] 1 H NMR (400 MHz, deuterated chloroform) δ8.70 (dd, 1H), 8.58 (s, 1H), 8.49–8.45 (m, 2H), 8.23–8.16 (m, 1H), 8.15–8.07 (m, 3H), 7.95–7.88 (m, 1H), 7.85 (dd, 1H), 7.75 (td, 2H), 7.71–7.62 (m, 4H), 7.53–7.43 (m, 3H), 7.43 (d, 1H), 7.40–7.29 (m, 7H), 7.25 (ddd, 1H), 7.19 (td, 2H), 2.27–2.23 (m, 6H).

[0108] Elemental analysis: Calculated value C, 68.51%; H, 4.22%; N, 4.89%. Test value C, 68.55%; H, 4.25%; N, 4.87%.

[0109] Preparation of Example 2G-12

[0110]

[0111] Step 1: The method for preparing intermediate S1 is the same as that in Example 1 to obtain S1.

[0112]

[0113] Step 2: The method for preparing intermediate S1 is the same as that in Example 1 to obtain S2.

[0114]

[0115] Step 3: Under nitrogen protection, weigh formula A-12 (81.85mmol), IrC13·3H2O (37.2mmol) and put them into the reaction system, add a mixed solution of 300ml ethylene glycol ethyl ether and 100ml pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, precipitate is precipitated, filter the precipitate, rinse and dry with water, anhydrous ethanol, and petroleum ether in turn. The bridged ligand B-12 (19.4g) is obtained, yield: 88.1%).

[0116] Step 4: Weigh the bridging ligand B-12 (16.38 mmol), add silver trifluoromethanesulfonate (36.03 mmol), then add 380 ml of dichloromethane to the system, add 126 ml of methanol, react at room temperature for 48 hours under nitrogen protection, pass through a silica gel funnel, and spin dry to obtain intermediate C-12 (22.4 g), yield: 89%.

[0117] Step 5: Weigh the intermediate C-12 (19.52 mmol), add the ligand S2 (48.8 mmol), and then add 300 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 72 hours, filter, wash with alcohol, and dry. Use a mixture of petroleum ether and dichloromethane as eluent, column chromatography, concentrate the filtrate, and solid precipitate to obtain the organic electroluminescent material G-12 (4.66 g, yield 26.92%).

[0118] HPLC: ≥99.3%.

[0119] Mass spectrometry test value: 887.47

[0120] 1 H NMR (400 MHz, deuterated chloroform) δ8.70 (dd, 1H), 8.62 (s, 1H), 8.47 (d, 2H), 8.19 (dd, 1H), 8.12 (d, 1H), 7.95–7.89 (m, 1H), 7.88–7.80 (m, 3H), 7.79–7.72 (m, 2H), 7.72–7.67 (m, 2H), 7.63 (d, 2H), 7.53–7.43 (m, 2H), 7.38–7.29 (m, 5H), 7.28–7.21 (m, 5H), 2.42 (s, 6H), 2.25 (d, 6H).

[0121] Elemental analysis: calculated values ​​C, 69.05%; H, 4.55%; N, 4.74%. Test values ​​C, 69.11%; H, 4.58%; N, 4.73%.

[0122] Example 3 Preparation of G-103

[0123]

[0124] Step 1: The method for preparing intermediate S1 is the same as that in Example 1 to obtain S1.

[0125]

[0126] Step 2: The method for preparing intermediate S1 was the same as in Example 1 to obtain S3 (9.97 g) with a yield of 48%.

[0127] Mass spectrometry test value: 345.37.

[0128]

[0129] Step 3: Under nitrogen protection, weigh formula A-103 (64.48 mmol) and IrC13·3H2O (25.79 mmol) into the reaction system, add a mixed solution of 150 ml of ethylene glycol ethyl ether and 50 ml of pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, precipitate, filter the precipitate, rinse and dry with water, anhydrous ethanol, and petroleum ether in turn. The bridged ligand B-103 (12.99 g) was obtained, with a yield of 94.02%.

[0130] Step 4: Weigh the bridging ligand B-103 (12.11 mmol), add silver trifluoromethanesulfonate (26.64 mmol), then add 240 ml of dichloromethane to the system, add 80 ml of methanol, react at room temperature for 48 hours under nitrogen protection, pass through a silica gel funnel, and spin dry to obtain intermediate C-103 (16.4 g), yield: 95.12%.

[0131] Step 5: Weigh the intermediate C-103 (23.03 mmol), add the ligand S3 (57.57 mmol), and then add 320 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 48 hours, filter, wash with alcohol, and dry. Use petroleum ether and dichloromethane as eluent, column chromatography, concentrate the filtrate, and solid precipitate to obtain organic electroluminescent material G-103 (7.51 g), yield: 38.62%.

[0132] HPLC:≥99.3%.

[0133] Mass spectrometry test value: 845.34.

[0134] 1H NMR (400 MHz, deuterated chloroform) δ 8.65–8.58 (m, 3H), 8.51 (q, 1H), 8.23–8.16 (m, 1H), 8.12 (d, 1H), 8.08 (dd, 2H), 7.92 (dd, 1H), 7.83 (dd, 2H), 7.77 (s, 1H), 7.75–7.68 (m, 4H), 7.53–7.47 (m, 2H), 7.46 (dd, 2H), 7.39–7.29 (m, 7H), 7.26 (ddd, 4.2, 1.4 Hz, 2H), 7.19 (td, 2H), 2.25 (s, 3H).

[0135] Elemental analysis: Calculated value C, 68.23%; H, 4.06%; N, 4.97%. Test value C, 68.26%; H, 4.13%; N, 4.93%.

[0136] Example 4 Preparation of G-181

[0137]

[0138] Step 1: The method for preparing intermediate S1 is the same as that in Example 1 to obtain S1.

[0139]

[0140] Step 2: Under a nitrogen atmosphere, the intermediate S1 (60.23 mmol), 4-methyl-2-pyridineboronic acid pinacol ester (72.27 mmol), potassium acetate (150.57 mmol), and 1,4-dioxane (2000 ml) were added into the phase system in sequence, and the nitrogen was replaced twice. Under nitrogen protection, tris(dibenzylideneacetone)dipalladium (0.6023 mmol) and X-Phos (4.8184 mmol) were added into the phase system, and the nitrogen was replaced twice. The reaction was heated to 100°C and refluxed for 12 hours. The heating was turned off, and the reaction was cooled to room temperature. The reaction was filtered, dried, passed through a silica gel funnel, rinsed with dichloromethane, and spin-dried to obtain the intermediate S4 (11.22 g). The yield was 54%.

[0141] Mass spectrometry test value: 345.29.

[0142]

[0143] Step 3: Under nitrogen protection, weigh formula A-181 (76.03mmol) and IrC13·3H2O (34.56mmol) into the reaction system, add a mixed solution of 300ml ethylene glycol ethyl ether and 100ml pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, precipitate is precipitated, filter the precipitate, rinse and dry with water, anhydrous ethanol, and petroleum ether in turn. The bridged ligand B-181 (18.7g) is obtained, with a yield of 87.26%).

[0144] Step 4: Weigh the bridging ligand B-181 (15.07 mmol), add silver trifluoromethanesulfonate (33.15 mmol), then add 360 ml of dichloromethane to the system, add 120 ml of methanol, react at room temperature for 48 hours under nitrogen protection, pass through a funnel, and spin dry to obtain intermediate C-181 (21.8), yield: 90.9%.

[0145] Step 5: Weigh the intermediate C-181 (18.14 mmol), add the ligand S4 (47.1 mmol), and then add 220 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 48 hours, filter, wash with alcohol, and dry. Use a mixture of petroleum ether and dichloromethane as eluent, column chromatography, concentrate the filtrate, and solid precipitate to obtain the organic electroluminescent material G-181 (6.14 g, yield 36.44%).

[0146] Mass spectrometry test value: 929.44

[0147] 1 H NMR (400 MHz, deuterated chloroform) δ 8.79–8.61 (m, 2H), 8.43 (dd, 2H), 8.24–8.07 (m, 2H), 7.97–7.85 (m, 1H), 7.76 (d, 1H), 7.64–7.60 (m, 2H), 7.57 (d, 2H), 7.52–7.45 (m, 3H), 7.37–7.30 (m, 5H), 7.14 (ddd, 1H), 7.08 (d, J=2.7 Hz, 2H), 6.85 (dd, 2H), 2.43–2.36 (m, 15H), 2.27–2.22 (m, 6H).

[0148] Elemental analysis: Calculated value C, 69.80%; H, 4.99%; N, 4.52%. Test value C, 69.81%; H, 5.02%; N, 4.54%.

[0149] Example 5 Preparation of G-471

[0150]

[0151] Step 1: The method for preparing intermediate S1 is the same as that in Example 1 to obtain S5.

[0152] 1 H NMR (400 MHz, deuterated chloroform) δ 8.12–8.04 (m, 3H), 7.90 (dd, 2H), 7.73 (d, 1H), 7.55–7.41 (m, 4H), 7.34–7.28 (m, 2H), 2.44 (d, 3H).

[0153]

[0154] Step 2: The method for preparing intermediate S2 is the same as that in Example 1 to obtain S6.

[0155] Rustic test value: 345.15.

[0156]

[0157] Step 3: Under nitrogen protection, weigh formula A-12 (81.85mmol), IrC13·3H2O (37.2mmol) and put them into the reaction system, add a mixed solution of 300ml ethylene glycol ethyl ether and 100ml pure water, reflux for 48 hours under nitrogen protection, then cool to room temperature, precipitate is precipitated, filter the precipitate, rinse and dry with water, anhydrous ethanol, and petroleum ether in turn. The bridged ligand B-12 (19.4g) is obtained, yield: 88.1%).

[0158] Step 4: Weigh the bridging ligand B-12 (16.38 mmol), add silver trifluoromethanesulfonate (36.03 mmol), then add 380 ml of dichloromethane and 126 ml of methanol to the system, react at room temperature for 48 hours under nitrogen protection, pass through a silica gel funnel, and spin dry to obtain intermediate C-12 (22.4 g), yield: 89%.

[0159] Step 5: Weigh the intermediate C-12 (19.52 mmol), add the ligand S6 (48.8 mmol), and then add 300 ml of anhydrous ethanol to the system. Under nitrogen protection, reflux for 72 hours, filter, wash with alcohol, and dry. Use a mixture of petroleum ether and dichloromethane as eluent, column chromatography, concentrate the filtrate, and solid precipitate to obtain the organic electroluminescent material G-471 (6.51 g, yield 37.02%).

[0160] HPLC: ≥99.3%.

[0161] Mass spectrum: 901.40

[0162] 1H NMR (400 MHz, deuterated chloroform) δ8.70 (dd, 1H), 8.62 (s, 1H), 8.47 (d, 2H), 8.22–8.17 (m, 1H), 8.13 (d, 1H), 7.95–7.89 (m, 1H), 7.88–7.80 (m, 3H), 7.79–7.73 (m, 2H), 7.73–7.67 (m, 2H), 7.63 (d, 2H), 7.53–7.43 (m, 4H), 7.34–7.28 (m, 2H), 7.28–7.21 (m, 5H), 2.42 (s, 6H), 2.38 (d, 3H), 2.25 (d, 6H).

[0163] Elemental analysis: Calculated value C, 69.31%; H, 4.70%; N, 4.66%. Test value C, 69.35%; H, 4.74%; N, 4.63%.

[0164] The synthesis methods of other organic electroluminescent materials G-3, G-22, G-35, G-55, G-142, G-254, G-336, G-363, G-406, G-423, G-478, G-512, G-542, G-567, G-621 and G-648 are the same as those in the above embodiments, and are not described in detail here. The molecular formulas or mass spectra of other synthesized organic electroluminescent materials are shown in Table 1 below:

[0165] Table 1 Molecular formula or mass spectrum of organic electroluminescent materials

[0166]

[0167]

[0168] Example 6: Fabrication of an organic electroluminescent device containing organic electroluminescent material G-2

[0169] The ITO glass substrate with a coating thickness of 150nm was cleaned twice in distilled water and ultrasonically washed for 30 minutes, and then repeatedly cleaned twice with distilled water and ultrasonically washed for 10 minutes. After the distilled water cleaning, ultrasonically washed with isopropyl alcohol, acetone, methanol and other solvents in sequence, and then dried and transferred to a plasma cleaning machine. The above substrate was washed for 5 minutes and sent to a vapor deposition machine.

[0170] First, 60 nm of 4,4',4"-tri[2-naphthylphenylamino]triphenylamine ("2-TNATA") was vacuum-deposited on the ITO (anode) as a hole injection layer; then 60 nm of N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB) was vacuum-deposited on the hole injection layer as a hole transport layer; and a light-emitting layer was vacuum-deposited on the hole transport layer. Among them, the main material of the light-emitting layer 4,4'-N,N'-biphenyl dicarbazole (CBP) and the doping material compound G-2 were in a weight ratio of 95:5 Mix and evaporate 30nm to form a light-emitting layer; then vacuum evaporate 10nm thick BAlq to form a hole blocking layer; then vacuum evaporate 40nm thick Alq3 on the hole blocking layer as an electron transport layer; then vacuum evaporate 0.2nm thick LiF on it as an electron injection layer; then vacuum evaporate 150nm thick Al on the electron injection layer as a cathode. This method is used to prepare an electroluminescent device. Under the condition of a certain brightness, the performance and luminescence characteristics of the obtained electroluminescent device are tested to evaluate the driving voltage, maximum external quantum efficiency and phosphorescence lifetime.

[0171] The material structure used in the device of the present invention is as follows:

[0172]

[0173] Comparative Example:

[0174] An organic electroluminescent device was prepared in the same manner as in Example 6, except that the doping material of the light-emitting layer was replaced with Compound 1 and Compound 2. The structure thereof is as follows:

[0175]

[0176] The prepared organic electroluminescent device was subjected to the same tests as those in device example 1. The results are shown in Table 2.

[0177] Table 2 Test results of organic electroluminescent devices

[0178] Compound Driving voltage(V) <![CDATA[Brightness (cd / cm 2 )]]> T95(h) EQE(%) Compound 1 4.54 1000 389 13.8 Compound 2 4.37 1000 402 15.7 G-2 3.90 1000 597 25.1 G-12 3.84 1000 632 26.3 G-103 3.86 1000 648 26.4 G-181 3.91 1000 650 27.1 G-471 3.83 1000 674 26.8 G-3 3.81 1000 642 27.6 G-22 3.89 1000 685 28.6 G-35 3.80 1000 691 31.5 G-55 3.84 1000 692 29.6 G-142 3.85 1000 703 30.8 G-254 3.83 1000 688 29.2 G-336 3.91 1000 676 29.6 G-363 3.82 1000 651 31.4 G-406 3.84 1000 696 28.9 G-425 3.77 1000 712 28.7 G-478 3.79 1000 701 31.4 G-512 3.89 1000 734 30.3 G-542 3.86 1000 696 29.3 G-567 3.97 1000 685 28.6 G-621 3.86 1000 672 29.6 G-648 3.85 1000 691 28.9

[0179] It can be seen from Table 2 that:

[0180] 1) By changing the degree of conjugation of the heterocyclic ligand, the driving voltage of the organic electroluminescent device prepared by using the organic electroluminescent material G-103 of the present invention is significantly reduced, the maximum external quantum efficiency is improved, and the life span is significantly improved compared with the comparative compounds 1 and 2.

[0181] 2) By introducing the same or different functional groups at different positions of the ligand, the conjugation effect is enhanced, so that after the organic electroluminescent material (such as G-2, G-12, G-181, G-471, etc.) prepared by the present invention is used in an organic electroluminescent device, the driving voltage is significantly reduced, the maximum external quantum efficiency is improved, and the life span is significantly improved.

[0182] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An organic electroluminescent material, characterized in that: The organic electroluminescent material has a structure shown in general formula I: Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 and R 23 Each is independently selected from any one or a combination of at least two of a hydrogen atom, a deuterium atom, a halogen atom, a cyano group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aralkyl group, a substituted or unsubstituted alkoxy group, a substituted or unsubstituted aryloxy group, a substituted or unsubstituted heteroaryloxy group, a substituted or unsubstituted heterocyclic group, a substituted or unsubstituted silanyl group, a substituted or unsubstituted germyl group, and a substituted or unsubstituted amino group; And R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 and R 23 They may optionally combine with adjacent groups to form a ring.

2. The organic electroluminescent material according to claim 1, characterized in that: The alkyl, aryl and aralkyl groups may be partially or fully deuterated.

3. The organic electroluminescent material according to claim 1 or 2, characterized in that: L A Ligand Select from the following structures:

4. The organic electroluminescent material according to any one of claims 1 to 3, characterized in that: L B Ligand Select from the following structures:

5. The organic electroluminescent material according to any one of claims 1 to 4, characterized in that: The organic electroluminescent material is preferably selected from the following two structural formulas I-1, I-2, I-3, I-4, I-5, I-6 or I-7:

6. The organic electroluminescent material according to any one of claims 1 to 5, characterized in that: The organic electroluminescent material is selected from any one of the following structures:

7. An organic electroluminescent device, characterized in that: The organic electroluminescent device comprises the organic electroluminescent material according to any one of claims 1 to 6.

8. The organic electroluminescent device according to claim 7, characterized in that: The organic electroluminescent device comprises: an anode, a cathode and an organic layer disposed between the anode and the cathode, wherein the organic layer comprises the organic electroluminescent material according to any one of claims 1 to 6; Preferably, the organic layer includes at least a hole injection layer, a hole transport layer, a layer having both hole injection and hole transport skills, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer and a layer having both electron transport and electron injection skills, or a combination of at least two of them.

9. The organic electroluminescent device according to claim 8, characterized in that: The organic layer comprises a light-emitting layer, and the light-emitting layer contains the organic electroluminescent material according to any one of claims 1 to 6.

10. The organic electroluminescent device according to claim 9, characterized in that: The light-emitting layer comprises a main material and a doping material, wherein the doping material is the organic electroluminescent material according to any one of claims 1 to 6; Preferably, the mixing mass ratio of the main material to the doping material is 90:10 to 99.5:0.5.